Origin of John’s Stone: A quartzitic boulder from the site of the 1908 Tunguska (Siberia) explosion; Icarus; Vol. 258 - Bonatti E. Enrico; Breger D. Dee; Tommaso D.R. Di Rocco; Fulvio F. Franchi; Luca G. Gasperini; Polonia A. Alina; Anfinogenov J. John; Anfinogenova Ya. J. Yana Jonovna (2015, 2015)
Title screen